Constructing highly stable dendritic silica-wrapped NiCo/carbon nanotubes architecture for hydrogen production. (November 2022) - Jing, F.; Pi, Y.; Zhao, C.; Zhou, H.; Luo, S.; Fang, W.
Abstract: Steam reforming of bio-sourced alcohols could produce renewable hydrogen, the most studied non-noble Ni catalysts are quite active, but usually suffer from fast deactivation due to the sintering of active sites and coke deposition during the reaction. The mesoporous silica with controlled thickness was thus assembled on the external surface of NiCo/carbon nanotubes (CNTs) to form a SiO2 @NiCo/CNTs sandwich-type structure. The presence of silica layer restricted efficiently the aggregation of metallic active sites owing to the confinement effect, and the thicker silica layer was more favorable to forming smaller particles whatever for the calcination or for the reaction processes. When it reached 25 nm, the particle size of the metallic active site kept nearly unchanged after the reaction. The coke resistance was improved as well, a negligible quantity of 0.01 mgC /gcat. was formed on SiO2 @NiCo/CNTs#3. Due to the simultaneous improvement in anti-sintering and coke resistance, the catalyst proved to very stable over a period of 35 h in the steam reforming of glycerol reaction. Graphical abstract: Image 1 Highlights: 1. Silica-metal nanoparticles-carbon nanotubes composite was successfully assembled 2. Thickness of dendritic silica layer could be easily tuned 3. The presence of silica layer did not affect the mass transfer 4. The confined nanoparticles contributed to the improvement of catalytic stability 5. It provided a universal strategy to prepare the highly stable reforming catalyst